Effect of AIB and substrates on the vegetative propagation of Dipteryx ferrea (Ducke) Ducke (shihuahuaco) in sub-irrigation chambre (Research, Society and Development, 2024)
This study aimed to develop an effective technique for the vegetative propagation of Dipteryx ferrea (Ducke) Ducke (shihuahuaco), seeking to obtain quality plants in a shorter time, given that the species faces challenges due to limited access to seed trees. Juvenile cuttings of 5 to 7 cm were used, treated with three concentrations of Indole-3-Butyric Acid (IBA): 8000 ppm (control), 12000 ppm, and 18000 ppm. The cuttings were placed in tubes with four substrates: Jiffy (control), coconut fiber (CF), carbonized rice husk + chicken manure compost (CRH+CM), and carbonized rice husk + sawdust compost (CRH+SD), and then distributed in trays in a sub-irrigation chamber. The analysis of variance showed significant differences in rooting depending on the substrate, with CAC+G (90.28%), Jiffy (84.72%), CF (80.56%), and CAC+A (62.50%) standing out. The best concentration of IBA was 18000 ppm, achieving 95.80% rooting when combined with CAC+G. It is concluded that IBA and substrates have a positive effect on the propagation of Dipteryx ferrea in environments such as the sub-irrigation chamber and using tubes.